2014
DOI: 10.1517/14740338.2014.975204
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions associated with antiretroviral therapy during pregnancy

Abstract: The benefits of ARV use during pregnancy outweigh the risks of adverse reactions identified to date. More studies are needed to assess the adverse effects in the medium- and long term in children exposed to ARVs during pregnancy, as well as pregnant women using lifelong antiretroviral therapy and more recently available drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
0
5
0
Order By: Relevance
“…Recent evidence raises concerns about the safety of certain antiretroviral drugs used in pregnancy, including increased risk for adverse birth outcomes [3,716], problems with pediatric growth and neurodevelopment [17] and future risk of cancer [6, 1820]. Also, HIV-exposed, uninfected (HEU) children have increased morbidity and mortality when compared with HIV unexposed, uninfected (HUU) children.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence raises concerns about the safety of certain antiretroviral drugs used in pregnancy, including increased risk for adverse birth outcomes [3,716], problems with pediatric growth and neurodevelopment [17] and future risk of cancer [6, 1820]. Also, HIV-exposed, uninfected (HEU) children have increased morbidity and mortality when compared with HIV unexposed, uninfected (HUU) children.…”
Section: Introductionmentioning
confidence: 99%
“…Phase 0 approaches could also be used to study adverse drug reactions (ADRs) such as cardiac mitochondrial dysfunction associated with doxorubicin mitochondrial DNA adduct formation, or potential for ZDV toxicity in neonates of mothers receiving antiviral therapy . The value of such limited‐exposure phase 0 human studies is further highlighted by the poor prediction of cardiotoxicity and other adverse effects of drugs from preclinical in vitro and animal models …”
Section: Past and Current Validation Efforts And Applicationsmentioning
confidence: 99%
“…16,59 The value of such limited-exposure phase 0 human studies is further highlighted by the poor prediction of cardiotoxicity and other adverse effects of drugs from preclinical in vitro and animal models. 60,61 Drug and biomarker localization Determining appropriate target exposure is one of the key objectives of drug development (Figure 1). 14 Due to methodological and technological limitations, however, drug PK has traditionally been investigated using plasma exposures.…”
Section: Drug-dna Adducts Mitochondrial Toxicity and Adverse Drug Rmentioning
confidence: 99%
“…Subsequently, other studies confirmed mitochondrial dysfunction as an important long-term effect of AZT alone and in combination with other nucleoside analogues that can manifest as a variety of clinical and laboratory abnormalities, including hematologic and liver function, myopathy, and CNS disorders [16,17]. Of utmost concern is the possibility that antiretroviral drugs could cause damage to the fetus, since drugs and other substances are typically transferred through the placenta to the fetus [18]. Blanche and colleagues [19] for example, described the effect of AZT on mitochondria and related them to neurological malformations, characterized by cortical and subcortical brain atrophy and hypersignaling of white matter, as well as neurologic-related symptomatology in newborns.…”
Section: Antiretroviral Therapy Adverse Effects In the Context Of mentioning
confidence: 99%